The acute post-activation performance enhancement of the bench press throw in disabled sitting volleyball athletes - Krzysztofik, M.; Matykiewicz, P.; Celebanska, D.; Jarosz, J.; Gawel, E.; Zwierzchowska, A. (International Journal of Environmental Research and Public Health, 2021)
The purpose of the present study was to examine the acute effects of the bench press exercise with predetermined velocity loss percentage on subsequent bench press throw (BPT) performance with raised legs or feet on the floor among disabled, sitting volleyball players. Twelve elite sitting volleyball athletes (age = 33 ± 9 years; body mass = 84.7 ± 14.7 kg; relative bench press maximum strength = 1.0 ± 0.3 kg/body mass) took part in this study. The experiment was performed following a randomized crossover design, where each participant performed a single set of bench press with a 60% one-repetition maximum (1RM) to a 10% decrease of mean bar velocity as a conditioning activity (CA). The BPT with a 60%1RM was performed to assess changes in peak power (PP), peak velocity (PV) before and after the CA. The differences between analyzed variables before and after the CA were verified using two-way repeated-measures ANOVA (condition × time; 2 × 2). The ANOVA showed a significant main effect of time for peak bar velocity (p = 0.03; ?2 = 0.312) and peak power output (p = 0.037; ?2 = 0.294). The post hoc comparison showed a significant increase in post-CA peak bar velocity and peak power for raised legs condition in comparison with pre-CA value (p = 0.02, p = 0.041, respectively). The present study showed that the subsequent BPT performed with raised legs could be enhanced by the bench press with a 60% 1RM to a 10% mean bar velocity decrease as a CA among disabled sitting volleyball players. Therefore, athletes and coaches can consider performing a bench press throw with raised legs without compromising performance.